KARAKTER GEOARKEOLOGIS DAN PROSES BUDAYA PRASEJARAH ZONA POROS PONJONG - RONGKOP DI BLOK TENGAH GUNUNGSEWU - , Jarwo Susetyo Edy Yuwono ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This thesis presents results of geoarchaeological research conducted in the Ponjong - Rongkop Axis Zone which is situated in the Central Block of Gunungsewu, a karstic area of the southern mountains of Java. This zone run north to south from Ponjong to Rongkop Districts forming an axis nearly perpendicular to the general orientation of Gunungsewu and is flanked by two former ancient lake depressions, the so-called Wonosari Basin and Baturetno Basin. Geomorphologically, it consists of a hilly karstic area. At the northern end lays a non-karst mountain which becomes the highest topography in the Central Block of Gunungsewu and the upstream region for the underground rivers of the Southern Mountains (Gunungkidul). Surveys in the zone has located at least 56 caves bearing archaeological potential. Seven of them were excavated and the results demonstrate prehistoric human occupation from the Late Pleistocene to Early Holocene. This research is addressed to contruct a model for human and landscape relationship in the Ponjong - Rongkop Axis Zone. Geoarchaeological approach, as an interdiciplinary study involving archaeology and geomorphology, is carried out to attain the research objectives which are two folds. Firstly, to explain the geoarchaeological character of the Ponjong - Rongkop Axis Zone that have been formed as a combination of some geomorphological aspects (morphology, morphogenetic, morphochronology, and morpho-arrangement) and archaeological aspects (distribution of caves with archaeological potential). This objective is achieved through assesment and mapping of the potential caves in the zone with regard to the local geomorphological aspects. Secondly, to explain the process of prehistoric culture, namely the cultural dynamic of the occupied caves and factors that influenced it. To attain this second objective, contextual analysis of the archaeological data and its stratigraphy which have been obtained from the archaeological excavations are conducted. Synthesis of the geoarchaeological characters and prehistoric cultural process provides an integrated explanation on the relationship between human and landscape in the research area as shown in three aspects: the landscape context and its changes, the formation and changes of the archaeological sites as well as the stratigraphic context